Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
( 1 , 2 )
Step-by-step explanation:
x + 4y = 9
x = 9 - 4y .... ( 1)
2x - 4y = -6 ...( 2)
substitute the 9 - 4y as x in the second equation
2( 9 - 4y ) - 4y = -6
distribute 2
18 - 8y - 4y = -6
combine like terms
18 - 12y = -6
Subtract 18 from both sides
18 - 18 - 12y = -6 - 18
- 12y = - 24
divide both sides by -12
-12y / -12 = -24/-12
y = 2
Now , substitute the 2 as y in the second equation
2x - 4y = -6
2x - 4 ( 2 ) = -6
2x - 8 = -6
add 8 to both sides
2x - 8 + 8 = -6 + 8
2x = 2
divide both sides by 2
2x / 2 = 2/2
x = 1.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.